The Influence of the Talaqqi Method in PAI Learning: Understanding the Science of Tajweed - Hamidah, Wanda; Guntur Cahaya Kesuma,; Agus Faisal Asyha,; Zahra Rahmatika, (Inspiratif Pendidikan, 2025)
This study aims to determine the effect of the Talaqqi method on students’ ability to understand the rules of tajwid in Grade VII at SMP Islam Kebumen Tanggamus. The research employed a quantitative approach with a one-group pretest–posttest design involving 32 students. Data were collected through oral tests, questionnaires, observations, interviews, and documentation. The findings show a significant improvement after the Talaqqi method was implemented. During the pre-test, which was conducted through an oral assessment, most students were still in the Poor category at 65.625 percent, while only 9.375 percent reached the Good category. After the application of the Talaqqi method, the post-test results also assessed orally showed substantial improvement, with 60 percent of students classified as Excellent, 36.67 percent as Good, and 3.33 percent as Fair. No students remained in the Poor category. The average score increased by 22.281 points with a significance level of 0.000, indicating that the Talaqqi method is effective in improving students’ ability to read the Qur’an according to tajwid rules.